Membangun Pendidikan Karakter melalui Pengimplementasikan Ecobrick pada Siswa di SMP Negeri 51 Pondok Bambu, Duren Sawit Jakarta Timur - Myta Widyastuti; Ida Rosida (Syntax Corporation Indonesia, 2024)
The increase in the number of people who are increasingly increasing and with a consumptive lifestyle causes several problems, one of which is the emergence of a lot of waste. Facing the problem of waste, recycling plastic waste is the best solution in overcoming it. Waste management is known as the